The platform transformation how IoT will change IT, and when - Perry, Matthew J. (O'Reilly Media, 2016)
While the full impact of the Internet of Things has yet to arrive, dozens of companies already offer IoT platforms with the services, software, and hardware necessary to make your company IoT-ready. How do you determine which platform will meet the needs of your industry and, more importantly, your business? This O'Reilly report will help you sort through criteria you need to think about when planning for the IoT. Author Matthew Perry explores key considerations for future-proofing elements of your IT stack and for smoothing the transition to IoT components. You'll not only examine the things and people you want to connect, but also the network upgrades necessary to connect them--including data flow, APIs and end user applications, and robust security. Chances are your IoT platform won't come out of a box; you may do part of the work internally. With the guidelines in this report, you'll learn how to prepare for an IoT platform that specifically meets the needs of your business and its customers.
Includes bibliographical references. - Online resource; title from title page (Safari, viewed June 12, 2018)
Keywords: Internet of things; Embedded Internet devices; Computer networks -- Security measures; Business enterprises -- Computer networks -- Management; Internet des objets; Internet intégré; Réseaux d'ordinateurs; Sécurité; Mesures; Entreprises; Réseaux d'ordinateurs; Gestion; Business enterprises; Computer networks; Management; Computer networks; Security measures